Canada : Financial Sector Stability Assessment. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
This report discusses key findings of the Financial Sector Stability Assessment on Canada. Canada's financial system successfully navigated the global financial crisis, and stress tests suggest that major financial institutions would continue to be resilient to credit, liquidity, and contagion risks arising from a severe stress scenario. Elevated housing prices and high household debt remain an area of concern, though targeted prudential and macroprudential measures are proving to be effective. The regulatory and supervisory framework is strong, and is complemented by a credible federal system of safety nets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet